Cerebral Venous Thrombosis in the Absence of Headache. Issue 1 (January 2015) - Coutinho, Jonathan M.; Stam, Jan; Canhão, Patricia; Barinagarrementeria, Fernando; Bousser, Marie-Germaine; Ferro, José M.
Abstract : Background and Purpose—: Although headache is the most common symptom in cerebral venous thrombosis, 5% to 30% of patients do not report headache at baseline. Characteristics of these patients have not been investigated. Methods—: In post hoc analysis of the International Study on Cerebral Vein and Dural Sinus Thrombosis study, patients who might not have been able to report headache (aphasia, stupor, coma, or mental status disorder) were excluded. Results—: Three hundred eighty-two of the original 624 patients (61%) were included, of whom 38 (10%) did not report headache at baseline. Patients without headache were older (mean age, 45 versus 37; P =0.001) and less often female (63% versus 77%; P =0.06). Paresis (42% versus 27%; P =0.05) and seizures (58% versus 32%; P =0.001) were more common in patients without headache, whereas papilledema was less common (8% versus 35%; P =0.001). Isolated cortical vein thrombosis (16% versus 2%; P =0.001), brain parenchymal lesions (66% versus 46%; P =0.02), and malignancies (18% versus 6%; P =0.009) were more common among patients without headache. Outcome at last follow-up was worse in patients without headache (modified Rankin Scale, 0–1; 76% versus 89%; P =0.04; mortality, 13% versus 5%; P =0.05), but after adjustment for prognostic variables, headache was not an independent predictor of outcome. Conclusions—: Patients with cerebral venous thrombosis but without headache are a heterogeneous subgroup, in which older patients, men, and some associated conditions are over-represented. Patients without headache had a worse clinical outcome, but after adjustment for imbalances, headache was not an independent predictor of outcome.